DIOCTOPHYMA RENALE IN DOGS (CANIS FAMILIARIS) IN URUGUAY - Hernández-Russo, Zully (2014)
Adults of Dioctophyma renale (Goeze, 1782) (Nematoda) can affect various domestic and wild mammals and occasionally humans. At this stage the nematode is found in the right kidney, but other aberrant locations have been reported. The purpose of this study was to report D. renale findings in dogs in Uruguay. The nematode was reported in canines with unspecific symptom of dioctophymosis and in two west coastal cities over the Uruguay River. We observed moving D. renale in the abdominal cavity and in the testicular bag when performing an ovariectomy and an orchiectomy. Parasite identification was based on the morphological characteristics, particularly size, color, reproductive structures especially in males. Accidental findings when performing surgical procedures confirm that one of the main forms of diagnosis increase the extra-renal casuistry. Dioctophymosis in dogs prompts considering preventive measures related to eating habits and to stimulate a responsible ownership, especially considering the potential risk of human infection.